2000
DOI: 10.1590/s0100-40422000000400020
|View full text |Cite
|
Sign up to set email alerts
|

Uma demonstração simples e visual do efeito do aquecimento com microondas em reações de poliadição

Abstract: A SIMPLE AND VISUAL DEMONSTRATION OF THE HEATING EFFECT OF MICROWAVES IN POLYADDITION REACTIONS.Polyaddition of commercial monomers is easily performed on a domestic microwave oven. The rate of polymerization depends on the structure of the monomer, power and time of irradiation. This methodology can easily be used to demonstrate the acceleration of organic reactions promoted by microwaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…It can be observed that higher extraction yields were obtained when the samples were dried in a vacuum oven, probably due to the more aggressive drying mechanism imposed on herbaceous samples in the microwave drier, which can evaporate some compounds. Some works in the literature ( , ) pointed out that unlike conventional heating, where a substance is heated from outside to inside, in a microwave oven, the substances absorb energy in several points and transfer it to the rest of the body. In this way, the heating is nonuniform and occurs from inside to outside of the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that higher extraction yields were obtained when the samples were dried in a vacuum oven, probably due to the more aggressive drying mechanism imposed on herbaceous samples in the microwave drier, which can evaporate some compounds. Some works in the literature ( , ) pointed out that unlike conventional heating, where a substance is heated from outside to inside, in a microwave oven, the substances absorb energy in several points and transfer it to the rest of the body. In this way, the heating is nonuniform and occurs from inside to outside of the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the agronomic variables on the quantitative content of the selected compounds were statistically analyzed by an analysis of variance coupled with a Tukey's test at a 5% confidence level. All statistical analysis were performed in the Statistica software (15).…”
Section: Methodsmentioning
confidence: 99%
“…17 A faixa de linearidade das isotermas de adsorção/dessorção de N 2 das argilas AB e ABMO se enquadrou na faixa de pressões relativas para a qual o método BET é indicado (0,03 a 0,35). 7 Os dados de análise textural dessas argilas estão mostrados na Tabela 2.…”
Section: Análise Textural Das Argilasunclassified
“…4 Paralelamente à aplicação de microondas como fonte energética, a última década testemunhou a crescente utilização de catálise heterogênea em reações orgânicas, 5 tendo as argilas sido empregadas com sucesso. 6,7 A grande área específica das argilas em conjunto com propriedades específicas, tais como capacidade de troca iônica e de aumento do espaçamento interlamelar, têm sido exploradas para sua aplicação como catalisadores. Com a combinação de microondas e catalisadores sólidos, ampliou-se a possibilidade de realização de reações em condições sem solventes.…”
Section: Introductionunclassified
“…Este pode acelerar de maneira significativa o tempo da reação, fornecendo bons rendimentos. Enaminocetonas foram preparadas a partir de β-dicetonas e diferentes aminas, utilizando montmorillonita ou sílica como suporte sólido, sob irradiação em microondas (VARMA et al, 1997;RECHSTEINER et al, 1993;SADICOFF et al, 2000).…”
Section: Planejamento De Fármacosunclassified